POTENSI ANCAMAN HILANGNYA KANDUNGAN MINERAL ALAMI (TENORM) DI WILAYAH PENGHASIL TAMBANG KABUPATEN BANGKA TENGAH - Hardiansyah, Jhoni; Samihardjo, Isroil; Santoso, Muhayatun (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
The community in Central Bangka Regency carried out an increase in illegal mining in 2021, which could potentially threaten the loss of strategic natural resources. Rocking table miners in Central Bangka Regency produce zircon sand, tin sand, monazite, ilmenite, and tailings, which are potential natural resources containing rare earth metal elements. This research aims to analyze the radioactive content of the minerals zircon sand, tin sand, monazite, ilmenite, and tailings as a threat to human health. The research showed that monazite samples from all villages still had a lot of rare earth metals in them, like yttrium (Y), lanthanum (La), cerium (Ce), samarium (Sm), neodymium (Nd), and gadolinium (Gd). The test results showed that monazite had the highest average concentrations of Rare Earth Elements (REEs), with values of 10.27±3% for La, 12.15±3% for Ce, 24.40±3% for Sm, 7.37±3% for Nd, and 0.69±3% for Gd. For tin samples, the average (Ce) was 2.79±3%, zircon samples had an average (Ce) of 4.33±3%, and (Nd) 1.04±3%. In the ilmenite samples, the average value (Y) was 6.64 ± 3%. Monazite has the most rare earth metal elements, but it has a very low selling price. Monazite plays a crucial role in safeguarding and preventing the loss of strategic natural resources and health threats. It provides policy advice to related institutions through various roles and functions, including investigation, early prevention, and forecasting of these threats.